(untitled) (Fiep Bulletin - online, 2012)
The quality of life is a subjective concept that refers to an individual’s perception about his position in life, in the context of culture and value systems in which he lives, and in relation to your goals, expectations, standards and concerns (WHOQOL Group, 1995). The goal of this survey is to review the key concepts that are derived from studies that focus on the theme of quality of life at work, through a narrative from antiquity until the present day. This is a bibliographic search, which brought together 17 thematic studies made available in computerized databases MEDLINE, CINAHL, LILACS, Scielo and manual query in journals and books in the area. This was accomplished in the period August 2007 to February 2008. As a result, we observed that the studies portray the definition of the quality of life as something complex. However, there is no denying that the measurement of the quality of life has great relevance to recent trends experienced in the working environment, which enables you to (re) know who is a worker, as he lives, how it works, among others, to implement public policies that guarantee rights arising from the working class struggle for the maintenance of employment.